Large cities in Poland in face of demographic changes - Gołata Elżbieta; Kuropka Ireneusz (Bulletin of Geography. Socio-Economic Series, 2016)
The growth of rural population, to the detriment of cities in Poland is caused mainly by agglomeration processes, including suburbanisation. Consequently, intense and sudden changes in demographic structure of large cities and surrounding regions are observed. The paper presents demographic changes in the largest Polish cities. The aim of the study was to verify whether the phenomenon of population aging was more distinct in large cities than in surrounding municipalities. We also aimed to answer the question of how changes in demographic processes should shape the social policy pursued by authorities in large cities. Discussion covers activities rising out of demographic challenges to meet the needs in the field of “services” for children and increasing demand for ventures related to care for the elderly. The analysis includes selected areas of the education, health care and social assistance fields.